PEMETAAN TREN PENELITIAN SHARIA COMPLIANCE PADA LEMBAGA KEUANGAN SYARIAH: STUDI BIBLIOMETRIK VOSVIEWER - Fauziyah, Nurul; Wulandari, Anggiani Sri (Jaksya: Jurnal Akuntansi Syariah, 2024)
This study examines the development trend of research related to sharia compliance in Islamic financial institutions during the period from 2014 to 2024. A search was conducted through Google Scholar in Perish/Harzing with the keyword "Sharia Compliance" to find relevant national journals. Based on the search results, 374 research articles were found which were then imported into the VOSviewer application. The analysis shows that 2022 recorded the highest publication with a total of 60 articles. Visual mapping was carried out with VOSviewer which classified research related to sharia compliance into 5 clusters and 68 items